2018
DOI: 10.15694/mep.2018.0000042.1
|View full text |Cite
|
Sign up to set email alerts
|

The flipped classroom in dental education - Learning beyond the four walls of the classroom

Abstract: Introduction: The 'Flipped Classroom' is a technology based approach, where the traditional class time and selfstudy activities are reversed or 'flipped'. In this model, low level cognitive skill like 'knowledge acquisition' are assigned to the students outside the classroom and activities that require higher cognitive skills like application and problem solving are done under the guidance of teacher in the classroom. We present a case study which was conducted at faculty of dentistry, Melaka Manipal Medical C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
(12 reference statements)
0
2
0
1
Order By: Relevance
“…Esto les ayuda a desarrollar habilidades transferibles que pueden aplicar en diferentes contextos (1,8). En el caso de las cualidades físico-mecánicas de los biomateriales odontológicos, el AI puede contribuir con los alumnos a desarrollar habilidades de diagnóstico y tratamiento; por ejemplo, los estudiantes pueden usar los conocimientos adquiridos para evaluar la condición de un diente y recomendar el material dental adecuado (1,(9)(10)(11)(12).…”
Section: Transformación Del Aprendizajeunclassified
“…Esto les ayuda a desarrollar habilidades transferibles que pueden aplicar en diferentes contextos (1,8). En el caso de las cualidades físico-mecánicas de los biomateriales odontológicos, el AI puede contribuir con los alumnos a desarrollar habilidades de diagnóstico y tratamiento; por ejemplo, los estudiantes pueden usar los conocimientos adquiridos para evaluar la condición de un diente y recomendar el material dental adecuado (1,(9)(10)(11)(12).…”
Section: Transformación Del Aprendizajeunclassified
“…Otras investigaciones sugieren la validez de esta metodología educativa en odontopediatría, ortodoncia, prostodoncia, radiología oral, anatomía y neuroanatomía (11). La clase invertida tiene la cualidad de potenciar la motivación de los estudiantes de odontología y optimizar su percepción de la calidad de la experiencia de aprendizaje (11,16,17).…”
Section: Aula Invertida En Odontologíaunclassified
“…The results showed that there was no significant difference in the examination score between flipped classroom and TBL, concluding that both styles are valid formats for clinical education compared to traditional lecture styles [ 22 ]. Likewise, other studies have suggested the validity of this educational method in pediatric dentistry [ 27 , 29 ], orthodontics [ 30 ], prosthodontics [ 31 ], oral radiology [ 32 ], anatomy and neuroanatomy [ 33 ], and biodiversity [ 34 ]. The flipped classroom has the potential to increase dental students’ motivation and improve their perception of the quality of the learning experience.…”
Section: Challenging the Traditional Teaching Of Dental Anatomymentioning
confidence: 99%
“…For example, the molar preparations will require restoration of the marginal ridges, contact points, occlusal and interproximal surfaces, and pits and fissures. The students will develop psychomotor (visual and motor) skills by waxing missing teeth structure and re-establishing proper morphology [ 5 , 31 , 35 , 36 ].…”
Section: Challenging the Traditional Teaching Of Dental Anatomymentioning
confidence: 99%